Facile method for the synthesis of Co-core Au-shell nanohybrid - Sardar, Debasmita; Neogi, S. K.; Bandyopadhyay, Sanjoy; Satpati, Biswarup; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (New Journal Of Chemistry, 2014)
Heterostructured Co-Au core-shell nanoparticles have been synthesized by reducing AuCl4- ions on cobalt nanoparticles after a minor but effective modification of cobalt surface by an amine. The core shell morphology is emphatically confirmed by thorough investigation through UV-Vis spectroscopy, X-ray photoelectron spectroscopy (XPS), and transmission electron microscopic analysis (TEM). The chemical composition and topography were determined using STEM-HAADF analysis and EFTEM imaging. Fourier transform infrared (FTIR) spectroscopy confirms the surface modification of Co nanoparticles and the interactions involved between the ligands and the core and shell metals at various steps of the synthetic process. The magnetic properties confirm the material to be superparamagnetic in nature.